PELATIHAN AKLIMATISASI TANAMAN HORTIKULTURA HASIL KULTUR IN VITRO GUNA MENINGKATKAN PENGETAHUAN DAN PENDAPATAN PETANI DI KELURAHAN SIMPANG PASIR - Faradilla Faradilla; Daryono Daryono; F. Silvi Dwi Mentari; La Mudi; Nur Hidayat; Riama Rita Manullang; Rusmini Rusmini; Roby Roby; Yuanita Yuanita; Zainal Abidin (BUDIMAS : JURNAL PENGABDIAN MASYARAKAT, 2023)
Partners in the application of community science and technology consisted of 10 farmers. The farmland is located in Simpang Pasir Village, Palaran District, Samarinda City. The problem faced by the partners is the poor quality of banana crops due to pest and disease attacks, resulting in many crops being damaged and less marketable as a result of reduced farmer income. The solution to this problem is to use plant tissue culture technology and utilize banana waste into compost. The purpose of community service activities is to provide knowledge about tissue culture cultivation and acclimatization as well as utilizing banana waste into planting media and compost. This activity was carried out from August to October 2023. The place of activity is in the nursery and farmland of farmers in Simpang Pasir Village, Palaran District, Samarinda City. The method used to solve partner problems is to provide an introduction and knowledge of plant propagation techniques in tissue culture, training in acclimatization of horticultural plant. Acclimatization is a critical stage in tissue culture so it requires knowledge and accuracy in its implementation so that plants grow well. The stages of the PKM program are the introduction of tissue culture techniques, providing material in presentations and video screenings. Training and assistance on how to acclimatize. The activity went well and smoothly with the enthusiastic welcome of the participants who participated in this activity and intended to practice it themselves in the field.